Lateral Heel Pain Caused by Impingement of Hypertrophic Peroneal Tubercle and Os Peroneum. (8th January 2021) - Takada, Ryosuke; Chang, Song Ho; Kasai, Taro; Naito, Masashi; Hirose, Jun; Tanaka, Sakae; Matsumoto, Takumi
Abstract : Hypertrophic peroneal tubercle (HPT) is an overgrowth of the peroneal tubercle located on the lateral aspect of the hindfoot, which could cause tenosynovitis of the peroneus longus tendon. Os peroneum (OP) is an accessory ossicle that exists in the peroneus longus tendon at the lateral aspect of the calcaneocuboid joint. Both HPT and OP can cause lateral foot pain and occasionally require surgical treatment. We encountered a case of lateral foot pain of HPT coexisting with OP. Careful preoperative magnetic resonance imaging, dynamic ultrasonographic image, and block injection suggested an impingement of HPT and OP as a cause of lateral foot pain. Surgical resection of HPT, while retaining OP, successfully achieved pain relief in the patient. To the best of our knowledge, this is the first report presenting a case of HPT coexisting with OP successfully treated without OP resection.